Pengaruh CSR Dan Kinerja Keuangan Terhadap Kinerja Lingkungan (Studi Kasus Pada Sektor Makanan Dan Minuman BEI 2021-2023) - Triseptya, Ghaliyah Nimassita; Sundari, Sri; Kartini (Bongaya Journal of Research in Accounting (BJRA), 2025)
The main goal of every company is to maximize profits. To achieve and maintain these performance results, the company will implement a strategy by running optimal performance. In addition to economic and social performance, environmental performance also receives serious attention from the community, where environmental issues are increasingly becoming important things that need to be considered for business sustainability. This study uses CSR and performance as independent variables, environmental performance as a dependent variable and company age as a control variable. Using 48 samples from the food and beverage sector on the IDX, and regression analysis using SPSS. The results of this study, CSR and financial performance do not affect